Implementation of Blended Learning in Higher Education during the COVID-19 Outbreak - Fiandra, Yudha; Giatman, Muhammad; Effendi, Hansi; Muskhir, Mukhlidi; Billet, Stephen (AI Society & STMIK Indonesia, 2022)
In the current COVID-19 transition period, effective learning model innovations are needed in all fields of education, especially higher education. This study aims to empirically verify the blended learning model applied in higher education during the covid 19 pandemic. Systematic iterature review and Meta-Analysis (PRISMA) were used as methods to conduct this research. The articles reviewed were 30 latest articles from 2019 to 2021. All articles were classified by author, year of publication, type of journal or conference, research methods used and supporting applications used in developing blended learning models. The results of the study are presented as follows. The results of the study found that the use of Moodle in the blended learning model is the most widely used in higher education today. The results of the study also prove an increase in the number of articles published from 2019 to 2020 and the most widely used research method in the current blended learning development model is literature review.